Dynamic proteomic changes and ultrastructural insights into Pochonia chlamydosporia’s parasitism of Parascaris equorum eggs - Hao, Luyao; Zhao, Fengmiao; Liu, Hongyou; Ma, Chengyu; Jia, Xiaoqing; Jiang, Lili; Fan, Zhaobin; Wang, Rui (Frontiers in Cellular and Infection Microbiology, 2025)
Pochonia chlamydosporia (Goddard) Zare & Gams (Ascomycota, Sordariomycetes, Hypocreales, Pochoniaceae, Pochonia) is a nematophagous fungus with significant potential as a biocontrol agent against animal-parasitic nematodes. However, the molecular and cellular mechanisms underlying its infection process remain poorly understood.This study comprehensively investigated P. chlamydosporia infection dynamics in Parascaris equorum eggs using both microscopic and proteomic approaches. Infection was monitored at three distinct stages (early, middle, and late). Microscopic analysis included scanning electron microscopy (SEM), transmission electron microscopy (TEM), and light microscopy (LM) to observe morphological changes. A 4D-DIA-based quantitative proteomics approach was employed to analyze exoproteomic changes, and quantitative PCR (qPCR) was used to validate key genes. Microscopic observations revealed progressive invasion of P. chlamydosporia into nematode eggs, with detailed morphological changes in both fungal structures and eggs, including key stages such as attachment, germination, and egg degradation. Proteomic analysis identified 410 differentially expressed proteins (DEPs) across the three stages, with 313 upregulated and 403 downregulated. Gene Ontology (GO) enrichment analysis showed DEPs involvement in cellular stress response, proteolysis, metabolic process, and hydrolase activity. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identified key pathways including signal transduction, cell wall biosynthesis, energy metabolism, and host-pathogen interactions. qPCR validation further supported the molecular basis of parasitic behavior. These findings clarify that P. chlamydosporia employs a highly coordinated molecular strategy to adapt to and exploit its host, contributing to our understanding of fungal-nematode interactions and laying a solid foundation for developing P. chlamydosporia as a sustainable tool for integrated pest management.